2014
DOI: 10.1371/journal.pone.0101638
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Focus on 3R Principles Reveals Major Reductions in the Use of Animals in Pharmaceutical Toxicity Testing

Abstract: The principles of the 3Rs, Replacement, Reduction and Refinement, are being increasingly incorporated into legislations, guidelines and practice of animal experiments in order to safeguard animal welfare. In the present study we have studied the systematic application of 3R principles to toxicological research in the pharmaceutical industry, with particular focus on achieving reductions in animal numbers used in regulatory and investigatory in vivo studies. The work also details major factors influencing these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 18 publications
1
114
0
4
Order By: Relevance
“…: (1) Medical research involving human subjects must conform to generally accepted scientific principles, be based on a thorough knowledge of the scientific literature, other relevant sources of information, and on adequate laboratory and, where appropriate, animal experimentation; (2) Appropriate caution must be exercised in the conduct of research which may affect the environment, and the welfare of animals used for research must be respected. The ethical use of animals in doing research should follow the instruction and recommendations of international standards (Grimm 2014;Guhad 2005; Törnqvist et al 2014). Russell and Burch (1959) were the first people that stated the idea of the use of animals in doing research which was expected to follow the rules of 3 R (The "three R principle").…”
Section: Bioethics In Biomaterials Researchmentioning
confidence: 99%
“…: (1) Medical research involving human subjects must conform to generally accepted scientific principles, be based on a thorough knowledge of the scientific literature, other relevant sources of information, and on adequate laboratory and, where appropriate, animal experimentation; (2) Appropriate caution must be exercised in the conduct of research which may affect the environment, and the welfare of animals used for research must be respected. The ethical use of animals in doing research should follow the instruction and recommendations of international standards (Grimm 2014;Guhad 2005; Törnqvist et al 2014). Russell and Burch (1959) were the first people that stated the idea of the use of animals in doing research which was expected to follow the rules of 3 R (The "three R principle").…”
Section: Bioethics In Biomaterials Researchmentioning
confidence: 99%
“…However, responding to the constant pressure in developing reliable and efficient alternative screening methods, many studies tried to predict the potential ENMs effects in vivo by analyzing their effects in vitro (Drasler et al, 2017;Braakhuis, 2015;Törnqvist et al, 2014;Bachler et al, 2015). We recently demonstrated that carbon based nanomaterials have distinct transcriptional MOA between in vivo and in vitro experimental settings and that commonalities are to be found by using comprehensive gene network models (Kinaret et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Growing pressures from major initiatives currently under way such as the European regulation REACH (Gleeson et al, 2012) and the widely-accepted adoption of the 3Rs principles (Replacement, Reduction and Refinement) for toxicity testing (Törnqvist et al, 2014) urge their replacement.…”
Section: Introductionmentioning
confidence: 99%